Adding Appropriate Fiber in Diet Increases Diversity and Metabolic Capacity of Distal Gut Microbiota Without Altering Fiber Digestibility and Growth Rate of Finishing Pig - Pu, Guang; Li, Pinghua; Du, Taoran; Niu, Qing; Fan, Lijuan; Wang, Huan; Liu, Hang; Li, Kaijun; Niu, Peipei; Wu, Chengwu; Zhou, Wuduo; Huang, Ruihua (Frontiers in Microbiology, 2020)
The digestion ability of pigs to dietary fiber is derived from their intestinal microbiota, especially hindgut microbiota. However, tolerance of pigs to high dietary fiber and the changes of microbiota profile with fiber levels are still unclear. To investigate the changes of gut microbiota with dietary fiber and its relationship with fiber digestibility, we conducted comparative analyses of growth rate, apparent fiber digestibility, gut microbiota and volatile fatty acid (VFA) profiles in Chinese Suhuai pigs feeding diets with different defatted rice bran (DFRB) fiber levels. We found that dietary fiber level had no effect on the growth rate of Suhuai pigs. Although the apparent digestibility of Cellulose, insoluble dietary fiber (IDF) and total dietary fiber (TDF) decreased with dietary fiber level, we found that the apparent digestibility of Cellulose, IDF and TDF of Suhuai pigs was not changed when provided with diet containing 19.10% TDF (as feed basis). The pigs provided with diet containing 19.10% TDF had higher microbial richness, proportions of several fiber-degrading bacteria taxa at genus level and predicted microbial functions (such as carbohydrate metabolism, energy metabolism) in cecum compared to those fed with basal diet. In addition, the fiber-induced increasing of fiber-degrading bacteria promoted the VFAs metabolism, which potentially helped Suhuai pigs to maintain growth rate. However, as TDF reached to 24.11% (as feed basis), the apparent digestibility of fiber decreased and the positive effect on intestine microbiota in caecum were absent. Together, our data suggest that appropriate fiber level could increase the diversity and metabolic capacity of distal gut microbiota to improve the utilization efficiency of fiber resources without altering the growth rate of pigs.